Hagar on Sinai: The Choice of Heracles, Mountain Women, and Pauline Allegory in Galatians - Friesen, Courtney J. P. (Journal of Biblical literature, 2025)
Paul's allegory of Hagar and Sarah in Gal 4:21-5:1 remains a perennial puzzle as its enigmatic chain of associations (two biblical women—two covenants—two geographical locations of Mount Sinai and Jerusalem) has no clear parallel. In this study, I offer a fresh perspective by exploring striking similarities with an allegorical parable that was widely popular across antiquity among Greeks and Romans and within Judaism and Christianity. The so-called Choice of Heracles—commonly attributed to Prodicus (Xenophon, Mem. 2.1.21-33)—also features two women as personified abstractions of two opposing moral principles. They are named "Virtue" and "Vice" and appear to Heracles as he is coming of age, deciding which road his life would take. The story's allegorical qualities enabled a remarkable range of adaptations for new scenarios, two of which stand out for their proximity to Paul. Philo of Alexandria reinvents and expands the Choice of Heracles for his exegesis of several opposing pairs of biblical mothers, including Hagar and Sarah, their sons, and respective inheritance rights (Sacr. 20-45). Dio Chrysostom reworks the myth for a political speech in which the two women—Royalty and Tyranny—are identified with eponymous mountain peaks upon which they sit (1 Regn. 49-84 [Or. 1]).